RETRACTED: GATA4 Regulates Inflammation-Driven Pancreatic Ductal Adenocarcinoma Progression - Jiang, Weiliang; Chen, Congying; Huang, Li; Shen, Jie; Yang, Lijuan (Frontiers in Cell and Developmental Biology, 2021)
Cancer-associated inflammation is a key molecular feature in the progression of pancreatic ductal adenocarcinoma (PDAC). GATA4 is a transcription factor that participates in the regulation and normal development of several endoderm- and mesoderm-derived tissues such as the pancreas. However, it remains unclear whether GATA4 is involved in the inflammation-driven development of pancreatic cancer. Here, we employed quantitative reverse transcription PCR, immunohistochemistry, and differential expression analysis to investigate the association between GATA4 and inflammation-driven PDAC. We found that overexpression of GATA4 in pancreatic tumor tissue was accompanied by increased levels of inflammatory macrophages. We used macrophage-conditioned medium to validate inflammation models following treatment with varying concentrations of lipopolysaccharide and determined whether GATA4-dependent inflammatory stimuli affected pancreatic cancer cell invasion and growth in vitro. Nude mouse models of dibutyltin dichloride-induced chronic pancreatitis with orthotopic tumor xenografts were used to evaluate the effect of the inflammatory microenvironment on GATA4 expression in vivo. Our findings indicate that overexpression of GATA4 dramatically aggravated inflammatory stimuli-induced pancreatic cancer cell invasion and growth via NF-κB and STAT3 signaling, whereas silencing of GATA4 attenuated invasion and growth. Overall, our findings suggest that inflammation-driven cancer progression is dependent on GATA4 expression and is mediated through the STAT3 and NF-κB signaling pathways.